Strategi Pengembangan Kurikulum dalam Pendidikan Islam : Strategies; Development; Curriculum; Islam - Setiawan, Hendra; Minarti, Sri (At-Tuhfah : Jurnal Studi Keislaman, 2024)
: In general, a person's religion is determined by the education, experience and training he or she received in childhood. The education he received in his childhood. Someone who does not receive religious education in his childhood will not feel the importance of religion in his adult life. life. It is different with people who have had religious experiences in their childhood, for example, their mother and father were religious people, their social environment and friends. who are religious, their social environment and friends also live religion, coupled with religious education at home, in society and at school systematically. Systematically. So, naturally, the person will have a tendency to live in religious rules, accustomed to practising religion. To live in religious rules, to be accustomed to worship, to be afraid of transgressing religious prohibitions, and to feel how pleasant religious life is. In fact, the curriculum is not just a set of technical instructions on subject matter. More than that, the curriculum is a planned and comprehensive programme that describes the quality of education of an institution, starting from the school level, sub-district level, district, province and nation. In itself, the curriculum plays a strategic role in the progress of the institution. The curriculum should not be static, because with the passage of time and the demands of life in society, the curriculum is always evolving and adapting to the progress of the times. Therefore, curriculum development must be pursued as a dynamic and integrative process, through curriculum development steps that are systematic, professional and include all aspects of the curriculum that are related to the achievement of national educational goals. This paper presents the steps of curriculum development.